Serotyping and antimicrobial resistance of Actinobacillus pleuropneumoniae isolates from fattening pigs in Poland from 2019 to 2024 - Przyborowska Paulina; Tobolski Dawid (BMC Veterinary Research)
Abstract Background Actinobacillus pleuropneumoniae is a prevalent respiratory pathogen causing substantial economic losses in swine production worldwide. The bacterium's ability to rapidly develop antimicrobial resistance (AMR) poses a significant challenge to effective treatment and control. In Poland, limited data on A. pleuropneumoniae serotype distribution and AMR patterns hinder evidence-based treatment strategies. This study examined the serotype diversity and AMR patterns of A. pleuropneumoniae isolates from porcine pleuropneumonia outbreaks in northeastern Poland between 2019 and 2024, providing crucial information for regional veterinary practices and antimicrobial stewardship efforts. Results Analysis of 119 isolates from 67 farms demonstrated the predominance of serotype 2 (65.5%), followed by serogroups 3, 6, 8 (18.5%) and 1, 9, 11 (15.1%). This distribution differs from recent trends in other European countries, suggesting regional epidemiological variations. High resistance rates were observed for tylosin (55.5%), gentamicin (36.1%), doxycycline (32.8%), and sulfamethoxazole/trimethoprim (26.1%). Multidrug resistance fluctuated between 14.3% and 21.9% over the study period, with no clear linear trend. From 2022 onwards, strains exhibiting resistance to seven or more antimicrobials, including cephalosporins, emerged, marking a significant shift in resistance profiles. Temporal analysis revealed diverse resistance patterns, with significant increases in some antimicrobials (e.g., sulfamethoxazole/trimethoprim, p = 0.001) and stability in others (e.g., tetracycline, p = 0.890). Notably, several antimicrobials, including florfenicol and colistin, maintained 100% efficacy against all isolates throughout the study period. Conclusions The findings highlight the dynamic nature of AMR development in A. pleuropneumoniae and underscore the need for ongoing surveillance in the region. The emergence of highly resistant strains, particularly those resistant to cephalosporins, raises concerns about future treatment options. These results can guide evidence-based treatment strategies and enhance antimicrobial stewardship efforts in regional swine production. Furthermore, the study emphasizes the importance of local AMR data in guiding antimicrobial use policies and the need for a coordinated approach to combat AMR in veterinary medicine.